2014
DOI: 10.1007/s00268-014-2760-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Antiplatelet Therapy on Patients Undergoing Gastroenterological Surgery: Thromboembolic Risks Versus Bleeding Risks During Its Perioperative Withdrawal

Abstract: Satisfactory outcomes were obtained during gastroenterologic surgery under rigorous perioperative management, including single-agent APT continuation in patients at high thromboembolic risk. Patients treated with multidrug APT still represent a challenging group, however, and need to be carefully managed to prevent perioperative complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
78
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 38 publications
(79 citation statements)
references
References 58 publications
1
78
0
Order By: Relevance
“…Although 5-year OS rates in APT group appeared to be lower than those of non-APT group, statistical analysis suggested that the reduced OS rates largely resulted from severe underlying disease including heart failure or cardiovascular disease, and were not related to APT. be performed safely and satisfactorily in patients with APT [8,9] . In addition, the current study also showed that the Kokura Protocol is valid and feasible even in the setting of colorectal cancer surgery, resulting in neither increased perioperative complications nor decreased DFS/OS of colorectal cancer patients receiving APT.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although 5-year OS rates in APT group appeared to be lower than those of non-APT group, statistical analysis suggested that the reduced OS rates largely resulted from severe underlying disease including heart failure or cardiovascular disease, and were not related to APT. be performed safely and satisfactorily in patients with APT [8,9] . In addition, the current study also showed that the Kokura Protocol is valid and feasible even in the setting of colorectal cancer surgery, resulting in neither increased perioperative complications nor decreased DFS/OS of colorectal cancer patients receiving APT.…”
Section: Discussionmentioning
confidence: 99%
“…We have established our own perioperative protocol ("Kokura Protocol") about antithrombotic agents and risk stratification using several guidelines concerning antithrombotics as references [8,9] . The perioperative management of antiplatelet agents is shown in Figure 1.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This case serves as an example of successful resolution of this challenging problem. in high thromboembolic risk patients ("Kokura Protocol") [2,3] , DAPT was discontinued 7 days prior to surgery and aspirin monotherapy was continued until surgery to minimize the risks of intraoperative bleeding and thromboembolic complications. We carried out left hepatectomy with Spiegel lobe resection, followed by biliary reconstruction ( Figure 1C).…”
Section: Introductionmentioning
confidence: 99%